How to support teachers to carry out educational robotics activities in school? The case of Roteco, the Swiss robotic teacher community - Mury, Sophia Reyes; Negrini, Lucio; Assaf, Dorit; Skweres, Melissa (Frontiers in Education, 2022)
The development of 21st-century transversal competences such as communication, cooperation, and creativity as well as computational thinking and programming may be aided through educational robotics (ER). Different countries have inserted ER in their school curricula, however to date ER activities are not carried out systematically in all schools and are more an initiative from single pioneer teachers. In Switzerland, to support all teachers to carry out ER activities and to foster the presence of ER in schools, a robotic teacher community (Roteco) has been created. Teachers may obtain assistance, share experiences, and access instructional resources through a digital platform, which will help them and spread the use of robotics in the classroom. For instance, the site enables educators to simply submit their activities, connect with other educators and professionals, choose and download didactic activities from their peers together with the relevant resources, and stay updated on the newest information, events, research, and further education courses in the field of ER. In the first years of the platform’s existence, already more than 1,400 teachers have joined it. The project and the findings of two surveys are presented in this publication. The first survey was carried out in 2020 with 87 teachers and the second one in 2021 with 48 teachers from the community. The findings highlight the community's greatest accomplishments as well as the motivations for teachers' recruitment into the Roteco community and their contributions to its expansion. The results of this project allow for discussion on how to support teachers to implement ER activities in schools in a systematic way.